The Influence of Electronic Health Record Demands, Information Overload, Turnover, and Technostress on Nurse Recruitment Policy at Budi Medika Hospital Bandar Lampung - Abid Akhmad Rasyid; Euis Mufahamah; Harold Kevin Alfredo (Harmoni Economics: International Journal of Economics and Accounting, 2026)
This study examines the influence of Electronic Health Record (EHR) demands, information overload, turnover, and technostress on nurse recruitment policy at Budi Medika Hospital Bandar Lampung. The implementation of digital health systems in hospitals has changed nurses’ work patterns, particularly through digital documentation, data input, system navigation, and technology-based administrative tasks. These changes may create additional workload and affect human resource management decisions, especially recruitment policy. This study used a quantitative explanatory approach with survey data collected from 100 nurses at Budi Medika Hospital Bandar Lampung. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The measurement model was evaluated through outer loading, Average Variance Extracted, Cronbach’s alpha, and composite reliability, while the structural model was assessed through R-square, Q² predictive relevance, and path coefficient testing. The results show that the model has strong explanatory power, with an R-square value of 0.836 and Q² value of 0.817 for nurse recruitment policy. The hypothesis testing results indicate that EHR demands have a positive and significant effect on nurse recruitment policy, with a path coefficient of 0.912, t-statistic of 16.500, and p-value of 0.000. Meanwhile, information overload, turnover, and technostress do not have significant direct effects on recruitment policy. These findings indicate that nurse recruitment policy in a digital hospital environment is mainly influenced by EHR-related work demands. Therefore, hospitals should not only recruit nurses based on clinical competence, but also consider digital readiness, EHR adaptability, and documentation competence as important recruitment criteria.